Morphology and histochemical analysis of glycoproteins in the digestive tract of Dabry's sturgeon. (28th February 2018) - Yang, S.; Wu, H.; Zhao, L. L.; Xiao, Q.; Fu, H. M.; Yang, S. Y.; Wang, Y.; He, Z.
Summary: The aim of this study is to explore the morphology and histochemistry of the digestive tract of Acipenser dabryanus (Duméril, 1869). The digestive system of the Dabry's sturgeon contained an oropharyngeal cavity, esophagus, stomach, pyloric caeca, duodenum, valvula intestine, and rectum. Both the pyloric caeca, and the valvula intestine, which belonged to elasmobranch, were present simultaneously in the digestive system of the Dabry's sturgeon, which indicated that it was an archaic species. According to the results, we found four types of mucous cells exist in the digestive tracts of the Dabry's sturgeon. The statistical results showed that there were various types and densities of mucous cells in different parts. In comparison, large quantities of mucous cells existed in intestines. The difference in type and distribution of mucous cells are closely related to the functions of the organs where they are found; 5‐hydroxytryptamine were used to identify the endocrine cells in the digestive tract of the Dabry's sturgeon.The 5‐hydroxytryptamine immunoreactive cells were distributed throughout the digestive tract except the esophagus.